Otobius megnini (Acari: Argasidae) in Iran: exotic or established? - Asadollah Hosseini Chegeni; Javad Khedri; Zakkyeh Telmadarraiy; Faezeh Faghihi (Persian Journal of Acarology)
Otobius megnini is a tick species which it's larvae and nymphs feed deep in the external ear canal of a variety of ungulates. In this study, twelve adult and four nymph specimens were collected from cattle hosts in Sistan and Baluchestan, and Hamedan Provinces. The specimens were identified using morphological key and the datawas confirmed by molecular assays. In the present study, we could find O. megnini in tick fauna of Iran with new hosts for this species.